Acid Pretreatment to Enhance Proton Transport of a Polysulfone‐Polyvinylpyrrolidone Membrane for Application in Vanadium Redox Flow Batteries. Issue 10 (24th August 2018) - Wu, Chunxiao; Zhang, Jin; Lu, Shanfu; Xiang, Yan; Jiang, San Ping
Abstract: An acid pretreatment strategy is developed to enhance the proton transport of polysulfone‐polyvinylpyrrolidone (PSF‐PVP) membranes for application in vanadium redox flow batteries (VRFB). The acid pretreatment leads to the formation of ionic conducting clusters with a size of around d=15.41  nm in the membrane ( p ‐PSF‐PVP). As a result, the proton conductivity and proton/vanadium ion selectivity of the p ‐PSF‐PVP membrane increases to 6.60×10 −2  S cm −1 and 10.63×10 7  S min cm −3, respectively, values significantly higher than 2.30×10 −2  S cm −1 and 6.67×10 7  S min cm −3 of the pristine PSF‐PVP membrane. Moreover, a VRFB assembled with the p ‐PSF‐PVP membrane exhibits a high coulombic efficiency of 98.6 % and an outstanding energy efficiency of 88.5 %. The results indicate that treatment with either sulfuric acid or phosphoric acid leads to an improvement of membrane properties, and the acid pretreatment is a promising strategy to significantly enhance the performance of the PSF‐PVP membrane for VRFB application. Abstract : Soaking it up : The proton transport and proton‐to‐vanadium ion selectivity of a polysulfone‐polyvinylpyrrolidone (PSF‐PVP) membrane can be improved by facile acid pretreatment. A vanadium redox flow battery fabricated with an acid pretreated PSF‐PVP membrane exhibits a high energy efficiency of 88.5 % at a current density of 60 mA cm −2 .